Strategi Peningkatan Motivasi Kerja Karyawan Pada Masa Efisiensi Anggaran Di Dinas Pariwisata Provinsi Sumatera Barat - Ayu Aprillia (Jurnal Ekonomi dan Bisnis Digital, 2025)
The goal of this research is to determine the strategies for improving employee work motivation during budget efficiency at the West Sumatra Provincial Tourism Office. This research uses a qualitative descriptive approach with data collection methods including interviews, observations, and documentation. The results of the study indicate that the work motivation strategies applied still need to be improved, especially under conditions of limited budgets. Several strategies such as providing non-material rewards, strengthening social relationships among employees, creating a positive work environment, and optimizing the achievement of Employee Work Targets (SKP) have been implemented but are not yet fully optimal. The imbalance between work demands and organizational support during efficiency measures causes employee motivation to remain fluctuating. Therefore, further efforts that are more structured are needed so that the strategies implemented can truly enhance employee motivation and performance.